Autoimmune hemolytic anemia due to mediastinal teratoma: A case report and review article - Maryam Ghazizadeh; Mohammad Moini; Matin Ghazizadeh (Clinical Case Reports, 2023)
Key Clinical Massage Autoimmune hemolytic anemia (AIHA) is a rare disease that is divided into primary and secondary types. In patients with AIHA we should consider mediastinal tumors as a serious cause. If such teratoma was found surgical removal of it is in order. Abstract Autoimmune hemolytic anemia (AIHA) is a rare disease that is divided into primary and secondary types. The secondary type usually appears as a complication to some diseases such as chronic inflammatory diseases, systemic lupus erythematosus (SLE), and malignancies. A 26 years‐old female with a chief complaint of weakness, fatigue, and exertional dyspnea is diagnosed with AIHA. Initially, medical steroid treatment appeared to be successful and the anemia improved, however, by weaning steroid dosage the disease relapsed. Eventually, surgical resection of the mediastinal teratoma lead to the hemolysis being treated successfully. In patients with AIHA we should consider mediastinal tumors as a serious cause. If such teratoma was found surgical removal of it is in order.